Preparation and Hydrodenitrogenation Performance of Ni2P/TiO2-Al2O3 Catalyst - Zhang, Jingru; Wang, Haiyan; Wei, Min (Asian Journal of Chemistry, 2013)
TiO2-Al2O3 composite support was prepared by the sol-gel process and then was used to prepare the precursors in oxidation state of Ni2P/TiO2-Al2O3 catalysts through wet impregnation method. The Ni2P/TiO2-Al2O3 catalyst was obtained via in situ hydrogen reduction technique in a fixed-bed reactor and its hydrodenitrogenation activity was tested using quinoline as model compound. Results showed that TiO2/Al2O3 molar ratios had a significant influence on hydrodenitrogenation activity as well as the loading of Ni2P. Catalyst exhibited the best catalytic activity when n(TiO2):n(Al2O3) was 1/4 and the loading of Ni2P was 25 wt % and its hydrodenitrogenation rate could reach 98.2 %.